2019
DOI: 10.3171/2018.5.jns1840
|View full text |Cite
|
Sign up to set email alerts
|

Staged bilateral pallidotomy for dystonic camptocormia: case report

Abstract: Camptocormia is a rare, involuntary movement disorder, presenting as truncal flexion while standing or walking, and is mainly observed as a feature of Parkinson’s disease (PD) and primary dystonia. Deep brain stimulation (DBS) of the globus pallidus internus is effective for refractory camptocormia observed with PD or dystonia. However, the effectiveness of pallidotomy for camptocormia has not been investigated. The authors report the case of a 38-year-old man with anterior truncal bending that developed when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, due to scarcity of literature, non‐English papers were also assessed. Finally, 33 papers met our inclusion criteria and were included in this review 15,17‐48 . The reasons to exclude the other 133 articles were the following: congress abstracts (n = 37), described no patients (n = 25), full text not available (n = 18), unilateral pallidotomy (n = 15), Parkinson's disease (n = 12), no (motor) outcomes (n = 9), patients described before (n = 7), thalamotomy or other lesions (n = 6), no dystonia patients (n = 2), and DBS only (n = 2) ( FIGURE S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to scarcity of literature, non‐English papers were also assessed. Finally, 33 papers met our inclusion criteria and were included in this review 15,17‐48 . The reasons to exclude the other 133 articles were the following: congress abstracts (n = 37), described no patients (n = 25), full text not available (n = 18), unilateral pallidotomy (n = 15), Parkinson's disease (n = 12), no (motor) outcomes (n = 9), patients described before (n = 7), thalamotomy or other lesions (n = 6), no dystonia patients (n = 2), and DBS only (n = 2) ( FIGURE S1).…”
Section: Resultsmentioning
confidence: 99%
“…Bilateral pallidotomy is quite effective for relieving isolated generalized dystonia in patients without CNS degeneration or insult, dystonic camptocormia, and status dystonicus. 29,[32][33][34][35][36][37][38] Bilateral lesioning is required to relieve axial dystonia, unlike in PD where even unilateral pallidotomy has reportedly had an effect on axial symptoms over time.…”
Section: Pallidotomy In Patients With Generalized Dystoniamentioning
confidence: 99%
“…Horisawa et al had a similar observation, with symptomatic improvement in dystonic camptocormia occurring 1 week after pallidotomy. 33 The long-term efficacy of pallidotomy in patients with dystonia is unknown, and there may be a relapse of symptoms after the initial response following pallidotomy. Ceneten et al reported relapse of symptoms in 19% of patients reported in the literature.…”
Section: Pallidotomy In Patients With Generalized Dystoniamentioning
confidence: 99%
“…PVP may be re-re-emerging also as a primary procedure in some countries such as Japan [38][39][40][41][42] and primarily thanks to the skills and confidence of neurosurgeons who had been trained or are being trained in performing PVP. Furthermore, even bilateral pallidotomy, especially for dystonia, is being revisited: last year a paper titled "Bilateral Pallidotomy for Dystonia: A Systematic Review" was published in Movement Disorders Journal by a Dutch team from Groningen [43].…”
Section: What Future For Posteroventral Pallidotomy?mentioning
confidence: 99%
“…PVP seems thus to be reported more and more in single cases or small case series, to treat dystonic storm [43, 44], including in pediatric patients [45], or other refractory conditions beyond the classical generalized or cervical dystonia or PD, such as embouchure dystonia [40] camptocormia [41], abdominal dystonia [46], hemichorea-ballism [47], or Meige syndrome [48]. Recently, PVP has even shown beneficial effect on the postherpetic neuralgic pain of a patient who had received a pallidotomy primarily for PD [49].…”
Section: What Future For Posteroventral Pallidotomy?mentioning
confidence: 99%